The relationship between speed and strength in the beach volleyball serve - Terol-Sanchis, M.; Elvira-Aranda, C.; Gómis-Gómis, M. J.; Pérez-Turpin, J. A. (Journal of Human Kinetics, 2021)
The objective of this study was to analyze the relationship between isometric force produced in different joints and its effects on the power kick serve speed in beach volleyball as a predictive aspect to improve sports performance. Seven athletes competing at national and international levels (mean ± standard deviation; age: 21.6 ± 3.20 years; body height: 1.87 ± 0.08 cm; body mass 80.18 ± 7.11 kg) were evaluated using maximum isometric force contractions (i.e., spinal and knee extension, grip by a hand dynamometer (handgrip), internal shoulder rotation, shoulder flexion, elbow flexion and extension, and wrist flexion). Speed of the ball was recorded with a pistol radar and force was measured with a strain gauge. Results showed a relationship between isometric force developed in the internal rotation of the shoulder and speed of the ball (r = 0.76*; p < 0.05). In the remaining isometric exercises, positive low to moderate correlations were found in the spine and knee extension (r = 0.56; p = 0.200) and elbow flexion (r = 0.41; p = 0.375). On the other hand, the remaining isometric exercises obtained weak or non-significant correlations. Force developed in the internal rotation of the shoulder highly correlated with the speed of the power kick, explaining, together with the elbow flexion and the extension of the knee and back, much of the variability of the power kick of beach volleyball athletes.